The Recycling Endosome in Nerve Cell Development: One Rab to Rule Them All? - Rozés-Salvador, Victoria; González-Billault, Christian; Conde, Cecilia (Frontiers in Cell and Developmental Biology, 2020)
Endocytic recycling is an intracellular process that returns internalized molecules back to the plasma membrane and plays crucial roles not only in the reuse of receptor molecules but also in the remodeling of the different components of this membrane. This process is required for a diversity of cellular events, including neuronal morphology acquisition and functional regulation, among others. The recycling endosome (RE) is a key vesicular component involved in endocytic recycling. Recycling back to the cell surface may occur with the participation of several different Rab proteins, which are master regulators of membrane/protein trafficking in nerve cells. The RE is comprised of a network of interconnected and functionally distinct tubular subdomains that originate from sorting endosomes and transport their cargoes along microtubule tracks, by fast or slow recycling pathways. Different populations of REs, particularly those formed by Rab11, Rab35, and Arf6, are associated with a myriad of signaling proteins. In this review, we discuss the cumulative evidence suggesting the existence of a heterogeneous population of REs, controlling different aspects of cell functions, with a particular focus on the commonalities and singularities of these different REs and their contribution to nerve development and differentiation in several animal models.